First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States - Macgown, Joe A.; Schiefer, Terence L.; Branstetter, Michael G. (Zootaxa, 2015)
We describe a new species of the Neotropical genus Leptanilloides, L. chihuahuaensis sp. n., based on male specimens from the Davis Mountains in western Texas. Known males of species of Leptanilloides are compared with L. chihuahuaensis. This is the first report of the genus from the United States and the Nearctic region. Previously, the Leptanilloides genus-group was only known to occur from southern Mexico to southeastern Brazil; and thus, this record from Texas represents a remarkable extension of the known range of the genus.